Hygrothermal Effect on MWCNT-Filled Epoxy Electrically Conductive Adhesives - Sheikh Md Fadzullah, Siti Hajar (Journal of Mechanical Engineering and Technology (JMET), 2020)
To-date, limited studies are found in the literature on the reliability performance of electrically conductive adhesive (ECA) using multiwalled carbon nanotube (MWCNT) fillers. Hence, this study aims to provide an understanding on the performance of the ECA with the objectives (i) to study the electrical conductivity and (ii) joint strength of ECA with varying conductive filler’s aspect ratio and environmental conditions. Here, epoxy with MWCNT aspect ratio of 55.5 and 1666.5 were subjected to 85°C and 85% RH for up to 96 hours. The test specimens were prepared in accordance with ASTM F390-11 using a four-point probe for electrical conductivity measurement while the lap shear test was conducted with reference to ASTM D1002-10 using a universal testing machine. For the thermal aging study, the ECA samples were conditioned in a humidity chamber at 85 °C and 85 % of relative humidity to assess the reliability performance of the ECA. Overall, it was found that ECA filled with higher aspect ratio of MWCNT exhibit better electrical and mechanical stability when subjected to hygrothermal aging. Moreover, the presence of moisture attack has yield in an increase in the electrical conductivity of the ECA with thermal aging period. Meanwhile, lap shear test results revealed a contradicting trend. Regardless of the amount of MWCNT filler loading, voids are created in the epoxy matrix of the ECA, which results in a decrease in the shear strength of the ECA, when the samples were subjected to thermal aging.